Export Control: Post-transcriptional Regulation of the COPII Trafficking Pathway - Bisnett, Brittany J.; Condon, Brett M.; Lamb, Caitlin H.; Georgiou, George R.; Boyce, Michael (Frontiers in Cell and Developmental Biology, 2021)
The coat protein complex II (COPII) mediates forward trafficking of protein and lipid cargoes from the endoplasmic reticulum. COPII is an ancient and essential pathway in all eukaryotes and COPII dysfunction underlies a range of human diseases. Despite this broad significance, major aspects of COPII trafficking remain incompletely understood. For example, while the biochemical features of COPII vesicle formation are relatively well characterized, much less is known about how the COPII system dynamically adjusts its activity to changing physiologic cues or stresses. Recently, post-transcriptional mechanisms have emerged as a major mode of COPII regulation. Here, we review the current literature on how post-transcriptional events, and especially post-translational modifications, govern the COPII pathway.